Preservation of freshness in flowers: A review of post-harvest challenges and solutions for traditional flowers - JAIN, RITU; HIREMATH, VARUN M; H R, RAGHAVENDRA; KUMAR, D LAVA; K, MADHAVI; M, VAMSI; TIWARI, A K; SINGH, BABITA; M, NAVEEN KUMAR; A, POOJA (The Indian Journal of Agricultural Sciences, 2025)
Traditional flowers are those commonly grown and used in religious, cultural, and ceremonial settings mostly in loose form, but also including certain cut flowers that hold deep cultural significance. In countries like India, loose flowers such as marigold, jasmine, chrysanthemum, and rose are integral to religious rituals, festivals, and social ceremonies. High perishability of these flowers makes them suffer substantial post-harvest losses, estimated at 30–40% in India, primarily due to inadequate handling, storage, and transportation infrastructure. While pre-harvest factors such as cultivation practices, plant health, and pest management influence initial flower quality, post-harvest conditions play a pivotal role in determining their shelf life and marketability. Recent advances in post-harvest technology have provided promising solutions to mitigate these losses. Techniques such as pre-cooling, modified atmospheric packaging, and the application of floral preservatives and growth regulators have proven effective in delaying senescence and reducing ethylene-induced deterioration. Furthermore, innovative approaches, including the use of nano-materials, melatonin treatments, essential oils, and biodegradable coatings, are being explored for their potential to extend vase life, reduce microbial contamination, and maintain visual and olfactory attributes of the blooms. This review highlights both traditional practices and state-of-the-art interventions aimed at preserving the quality of harvested flowers, with an emphasis on scalable and sustainable technologies suitable for enhancing the longevity and commercial viability of traditional floral species.